The coming war of logistics - Till, Geoffrey (2022)
As the Russian invasion of the Ukraine moves into its second phase, the battle for supplies will become increasingly crucial. The outcome of this logistic campaign will determine events in the Ukraine, the future of the European security order and will have global consequences.